2015
DOI: 10.1016/j.freeradbiomed.2014.09.027
|View full text |Cite
|
Sign up to set email alerts
|

Redox regulation of Rac1 by thiol oxidation

Abstract: The Rac1 GTPase is an essential and ubiquitous protein that signals through numerous pathways to control critical cellular processes, including cell growth, morphology, and motility. Rac1 deletion is embryonic lethal, and its dysregulation or mutation can promote cancer, arthritis, cardiovascular disease, and neurological disorders. Rac1 activity is highly regulated by modulatory proteins and posttranslational modifications. Whereas much attention has been devoted to guanine nucleotide exchange factors that ac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
51
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 36 publications
(52 citation statements)
references
References 87 publications
1
51
0
Order By: Relevance
“…The inability of antioxidants to induce migratory and invasive phenotypes in the presence of BSO indicates that glutathione biosynthesis, not just GSSG reduction, is necessary for the effect. Changes in redox status also reportedly alter nucleotide binding by the RHO family of GTP-ases 45, 46, 79 . GTP loading of RHOA but not RAC1 increases consistently following treatment with antioxidants like NAC and the vitamin E analog Trolox.…”
Section: Mitochondrial Ros Contributes To Melanoma Metastasismentioning
confidence: 96%
“…The inability of antioxidants to induce migratory and invasive phenotypes in the presence of BSO indicates that glutathione biosynthesis, not just GSSG reduction, is necessary for the effect. Changes in redox status also reportedly alter nucleotide binding by the RHO family of GTP-ases 45, 46, 79 . GTP loading of RHOA but not RAC1 increases consistently following treatment with antioxidants like NAC and the vitamin E analog Trolox.…”
Section: Mitochondrial Ros Contributes To Melanoma Metastasismentioning
confidence: 96%
“…S4 and table S1). RHO family proteins RHOA and RAC1 mediate cytoskeletal changes during cell migration and invasion, and recent studies indicate that they are regulated by the cell's redox status through direct modification of residues involved in nucleotide binding (16)(17)(18). We therefore determined whether antioxidants affect the activation of RHOA and RAC1.…”
Section: Effects Of Nac and Trolox On Cultured Human Melanoma Cellsmentioning
confidence: 99%
“…Such a scenario is the case for Rac1, which has been shown to be activated by ROS/RNS both in vitro [138, 140] and in cellulo [139142]. Early work by Heo and colleages [138] showed that the dramatic increase in Rac1 nucleotide dissociation induced by O 2 •− in vitro has no effect on a Rac1 C18S mutant, suggesting that activation of Rac1 is due to direct oxidation at Cys18.…”
Section: The Actin Cytoskeleton As a Target Of Oxidantsmentioning
confidence: 99%